Production prices and distribution frontiers for the colombian economy in 1980 (1992)
Following the classical-Marxian tradition, a lineal model ofproduction based on an open Leontief system is used in thisstudy to calculate labor values, direct prices and productionprices for the colombian economy in 1980. In addition, boththe average profi t margin and the real wage rate were estimated in order to derive at the Sraffian wage-prafit frontiers. The results show, on the one hand, that the deviations between direct values ar prices and the market prices are less significant that those existing between production prices and market prices. On the other hand, that the wage-profit frontiers estimated indicate that income distribution is highly favorable to the capitalistic class and, furthermore, that the reswitching of production techniques does have an empirical feasibility in Colombia.